2017
DOI: 10.11604/pamj.2017.26.41.10975
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, aetiology and antibiotic sensitivity profile of asymptomatic bacteriuria isolates from pregnant women in selected antenatal clinic from Nairobi, Kenya

Abstract: IntroductionAsymptomatic bacteriuria (ASB) is the presence of bacteria in urine without apparent symptoms of urinary tract infections. The importance of asymptomatic bacteriuria lies in the insight it provides into symptomatic infections. To determine prevalence, bacterial isolates and Antibiotic Sensitivity Profile of asymptomatic bacterial urinary tract infection in pregnant women in selected clinics in Nairobi.MethodsThis was a cross-sectional study involving women attending antenatal clinic at selected cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
37
6
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(99 citation statements)
references
References 27 publications
26
37
6
11
Order By: Relevance
“…All the gram-negative isolates except Acinetobacter showed resistance in the range of 89% -100% to Ampicillin and Sulfamethoxazole-Trimethoprim (SXT). These results are similar to those published in two related studies in Kenya indicating that E. coli obtained in Kenya are more resistant to these antimicrobials than among similar isolates encountered in developed countries such as Japan [19]. This is particularly worrying because Sulfamethoxazole/Trimethoprim is heavily relied upon as a prophylaxis against opportunistic infections among individuals infected with HIV in Kenya.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All the gram-negative isolates except Acinetobacter showed resistance in the range of 89% -100% to Ampicillin and Sulfamethoxazole-Trimethoprim (SXT). These results are similar to those published in two related studies in Kenya indicating that E. coli obtained in Kenya are more resistant to these antimicrobials than among similar isolates encountered in developed countries such as Japan [19]. This is particularly worrying because Sulfamethoxazole/Trimethoprim is heavily relied upon as a prophylaxis against opportunistic infections among individuals infected with HIV in Kenya.…”
Section: Discussionsupporting
confidence: 88%
“…An alarming finding in this study was the high prevalence of resistance to third generation Cephalosporins among the Gram-negative uropathogens. An earlier study done in Kenya reported similar resistance patterns in uropathogens [19]. This could be attributed to the presence of co-selection of genes conferring resistance to these antibiotics as well as issuance of prescriptions without susceptibility data.…”
Section: Discussionmentioning
confidence: 64%
“…The second most common isolated organism was Staphylococcus aureus. This is agreement with other studies [4,14] in which Staphylococcus aureus was the second most commonly isolated Uropathogen. However, it disagrees with other studies [27]in which Staphylococci was the most commonly isolated organism.…”
Section: Plos Onesupporting
confidence: 93%
“…Asymptomatic bacteriuria in pregnancy (ASBP) is defined as presence of bacteria in urine of quantitative counts of 10 5 colony forming units/mL without signs and symptoms of urinary tract infection [1]. Globally the prevalence of ASBP is estimated to be 2-11%, although higher rates have been reported in Uganda [3,4]. Women at increased risk of ASBP include women with diabetes mellitus and gestational diabetes, women of low socioeconomic status and past history of urinary tract infection [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation